Effect of Artemisinin on the Redox System of NADPH/FNR/Ferredoxin from Malaria Parasites - Yoko Kimata-Ariga; Rena Morihisa (MDPI AG, 2022)
FNR and ferredoxin constitute a redox cascade, which provides reducing power in the plastid of malaria parasites. Recently, mutation of ferredoxin (D97Y) was reported to be strongly related to the parasite's resistance to the front-line antimalarial drug artemisinin. In order to gain insight into the mechanism for the resistance, we studied the effect of dihydroartemisinin (DHA), the active compound of artemisinin, on the redox cascade of NADPH/FNR/ferredoxin in in vitro reconstituted systems. DHA partially inhibited the diaphorase activity of FNR by decreasing the affinity of FNR for NADPH. The activity of the electron transfer from FNR to wild-type or D97Y mutant ferredoxin was not significantly affected by DHA. An in silico docking analysis indicated possible binding of DHA molecule in the binding cavity of 2'5'ADP, a competitive inhibitor for NADPH, on FNR. We previously showed that the D97Y mutant of ferredoxin binds to FNR more strongly than wild-type ferredoxin, and ferredoxin and FNR are generally known to be involved in the oxidative stress response. Thus, these results suggest that ferredoxin is not a direct target of artemisinin, but its mutation may be involved in the protective response against the oxidative stress caused by artemisinin.